Effect of halloysite nanotubes on water absorption and mechanical characteristics of cellulose fibre reinforced epoxy composites in wet conditions - Alamri, Hatem; Low, It Meng (Asian-Australasian Association for Composite Materials (AACM), 2012)
The effect of halloysite nanotubes (HNTs) on enhancing the moisture barrier and mechanical properties of cellulose fibre (CF) reinforced epoxy composites after water treatment for six months was investigated. Results showed that water uptake decreased as HNT contents increased. The presence of HNT improved flexural strength, flexural modulus and fracture toughness of CF/epoxy composites. Scanning electron micrographs showed severe damage in fibre-matrix interfacial bonding due to water absorption. The addition of HNT was found to enhance to adhesion between fibre and matrix.